A study of back strength, leg strength and leg power among freshmen high school boys in two secondary schools in Baguio City - Castro, Pedro F. 1940- (1978)
The researcher of this study felt the need to investigate whether strengthening a body part significantly strengthens other body parts. Specifically, the researcher wanted to study the relationships of the strength of the back muscles, leg muscles, and leg power. The normative and descriptive forms of investigation were extensively used. The subjects were 215 freshmen boys from two secondary schools in Baguio. The findings concluded that strength and power of the legs and back have no significant relationship, and therefore, strengthening one of these does not strengthen the other.
Vita.
Thesis (M.A.T. Physical Education)--University of the Philippines, Diliman.
Keywords: Back exercises -- Philippines -- Baguio City (Benguet); Leg exercises -- Philippines -- Baguio City (Benguet); High school boys -- Philippines -- Baguio City (Benguet); Physical education and training -- Philippines -- Baguio City (Benguet); Muscle strength